Benefits of dietary fibre for human health and eating habits in different countries - Leal, Marcela (2017)
Background and Objectives: Because DF has unequivocally demonstrated many benefits for the human health, its consumption should be encouraged. In this way, this research aimed at identifying the eating habits regarding fibre rich foods and assessing the knowledge about the effects of DF as enhancers of human wellbeing. The study was undertaken simultaneously in five countries situated in different parts of the globe, namely South America (Argentina), Africa (Egypt), South Europe (Italy), Central Europe (Romania) and North Europe (Latvia). Methods: A descriptive cross-sectional study was carried out on a non-probabilistic sample of 2290 participants from 5 countries. The data collection was made by a questionnaires translated into the native languages in all participating countries. Results: The consumption of vegetables and salads was higher for Argentina and lower for Egypt while fruits are more consumed in Italy and less in Latvia. Whole grains are more consumed in Latvia and Romania and less in Argentina and Italy. The knowledge about the benefits of DF for cardiovascular diseases and cholesterol is higher in Argentina, for bowel cancer and diabetes in Romania and for obesity and constipation in Latvia. Still, an important number of participants do not have opinions about the different health benefits of DF. Conclusions: In general, the participants showed a moderate consumption of vegetables and fruits but low in whole cereals. The level of knowledge about the effects of DF on human health is still far from desirable levels, and differs considerably from country to country.